MY SAY: How to create an enlightened society - Abd Razak, Dzulkifli (2008)
So, some Malaysians finally got what they wanted pop star Avril Lavigne performing a concert in Kuala Lumpur. Earlier, she had been considered "unsuitable", especially since the show was scheduled to take place two days before the National Day celebrations. Undeniably, it was a night to remember, especially for most of the fans. There was another event that took place that captured the hearts and minds of a larger crosssection of Malaysians. It was the visit of former Indian president Dr A P J Abdul Kalam to Malaysia, which began just a day before Avril's concert.